PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK LAPTOP ASUS PADA KONSUMEN SANTRI PONDOK PESANTREN MAHASISWA (PPM) AR-ROYYAAN BAITUL HAMDI YOGYAKARTA - Shelgy Muharyo; Pahlevi, Reza Widhar (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to examine the effect of product quality and price on purchasing decisions for Asus laptop products on the Ar-Royyaan Baitul Hamdi Islamic Boarding School (PPM) Consumers in Yogyakarta. This study uses a quantitative research approach with multiple linear regression method. The variables used are Product Quality, Price, Purchase Decision. The type of data used in this study is primary data taken directly by distributing questionnaires, namely the Consumers of the Ar-Royyaan Baitul Hamdi Islamic Boarding School Students (PPM) Yogyakarta. The results of this study indicate that product quality and price have a significant effect on purchasing decisions on Ar-Royyaan Baitul Hamdi Islamic Boarding School Students (PPM) consumers in Yogyakarta